2014
DOI: 10.1093/abbs/gmt140
|View full text |Cite
|
Sign up to set email alerts
|

ERK1/2 mediates lung adenocarcinoma cell proliferation and autophagy induced by apelin-13

Abstract: The aim of this study was to investigate the role of apelin in the cell proliferation and autophagy of lung adenocarcinoma. The over-expression of APJ in lung adenocarcinoma was detected by immunohistochemistry, while plasma apelin level in lung cancer patients was measured by enzyme-linked immunosorbent assay. Our findings revealed that apelin-13 significantly increased the phosphorylation of ERK1/2, the expression of cyclin D1, microtubule-associated protein 1 light chain 3A/B (LC3A/B), and beclin1, and conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 52 publications
3
61
2
Order By: Relevance
“…Xie et al [22] indicated that static pressure up-regulated APJ expression to promote cardiomyocyte hypertrophy by autophagy pathway. Yang et al [7] also confirmed that apelin-13 promote autophagy via ERK1/2 signaling pathway. In the present study, we observed the effects of apelin/APJ on the autophagy.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Xie et al [22] indicated that static pressure up-regulated APJ expression to promote cardiomyocyte hypertrophy by autophagy pathway. Yang et al [7] also confirmed that apelin-13 promote autophagy via ERK1/2 signaling pathway. In the present study, we observed the effects of apelin/APJ on the autophagy.…”
Section: Discussionmentioning
confidence: 87%
“…Functionally, apelin can stimulate cell proliferation [6][7][8]. Apelin can promote thymidine incorporation into the DNA in Chinese hamster ovary (CHO) cells.…”
Section: Introductionmentioning
confidence: 99%
“…It is knowledgeable that adhesion, proliferation [53][54][55] , migration [56] and autophagy [57,58] are the characteristics of cells [59][60][61] . [61] .…”
Section: Endoplasmic Reticulum Stress Regulates Cardiovascular Physiomentioning
confidence: 99%
“…Moreover, in our experiments a modest increase in pressure suggests that apelin is not always one of the strongest inotropic compounds as sometimes it has been reported [74,41]. On the other hand, chronic apelin administration may be a key factor leading to tumorigenesis [117,118]. Independently of the duration and intensity of the effect on contractility, it must be kept in mind that at present the use of inotropic drugs is quite limited, because of their poor long term therapeutic effectiveness.…”
Section: Is Apelin a Therapeutic Tool?mentioning
confidence: 47%